ASSESSING THE EFFICACY OF DANSHENFORM COMPOUND IN PATIENTS WITH STABLE ANGINA PECTORIS - Hassan, Mahmood ul; Qureshi, Saqib; Hussain, Chiragh; Gul, Adnan Mehmood; Hafizullah, Mohammad (Journal of Postgraduate Medical Institute, 2011)
Objective : To assess the efficacy of danshenform compound in patient with angina pectoris already on optimal dose of anti anginal therapy assessed by exercise tolerance test. Methodology th week recorded. Total exercise time, onset of chest pain during exercise, onset of ST segments depression before and after treatment with Danshenform compound was recorded. : Thirty eight patients with stable angina were included in the study. Patients were exercised on treadmill according to Bruce protocol at baseline and one week later. At second week, Danshenform compound 500 mg was prescribed bid for four weeks. At the end of 4 weeks, exercise tolerance test was performed. Duration and number of anginal episodes before and at the end of 4th week recorded. Total exercise time, onset of chest pain during exercise, onset of ST segments depression before and after treatment with Danshenform compound was recorded. Results : The number of anginal episodes after 4 weeks treatment with danshenform was reduced significantly from 4.2+2.4 to 1.4+1.6/week (p=0.001). Time of onset of chest pain improved from 4.63+2.4 to 5.4+3.7 minutes (p=0.35) on exercise tolerance test. Duration of exercise increased from 6.52+1.9 minutes to 8.32+2.3 (p=0.001).Time of onset of ST depression increased from 5.8+1.7 to 7.7+1.6 minutes (p=0.001) on stress test. Anginal class improved significantly after 4 weeks of treatment with danshenform compound (p=0.001) with no significant effect on resting heart rate (p=0.58) and systolic blood pressure (p=0.07) respectively. Conclusion : Danshenform compound is useful in reducing anginal episodes, increasing exercise duration, improving functional anginal class, delaying the onset of ST depression on exercise tolerance test in patient with ischemic heart disease.